A Fuzzy Markov approach for assessing groundwater pollution potential for landfill siting - Chen, WY; Kao, JJ (My University, 2002)
This Study presents a Fuzzy Markov groundwater Pollution potential assessment approach to facilitate landfill siting analysis. Landfill siting is constrained by various regulations and is complicated by the uncertainty of groundwater related factors. The conventional static rating method cannot properly depict the potential impact of Pollution on a groundwater table because the groundwater table level fluctuates. A Markov chain model is a dynamic model that can be viewed as a hybrid of probability and matrix models. The probability matrix of the Markov chain model is determined based on the groundwater table elevation time series. The probability reflects the likelihood of the groundwater table changing between levels. A fuzzy set method is applied to estimate the degree of pollution potential, and a case study demonstrates the applicability of the proposed approach. The short- and long-term pollution potential information provided by the proposed approach is expected to enhance landfill siting decisions.
Keywords: landfill siting; groundwater table; fuzzy set; Markov chain; dynamic system; wmr 485-5